Peran Guru Pendidikan Agama Islam dalam Membangun Semangat Keberagaman Beragama di SMPN 13 Kota Kupang - Zikry Septoyadi; Vita Lastriana Candrawati; Adi Ahmad Rezal; Junanah Junanah (Transformatif, 2021)
This research was started when the writer felt uneasy about cases concerning religious issues that have recently occurred in Indonesia. Either on purpose or not. Now there are a lot of certain people who become elements of a problem regarding religion in Indonesia, as well as when certain groups have liberal beliefs where they lack socialization in society. This study aims to describe the perspectives of an Islamic Education teacher and also the principle of religious diversity in schools. The type of research used is descriptive qualitative. Where the researcher looks for several sources and then puts them together and in the sense that the research is meant to gather information about the status of an existing symptom. The data collection technique was done by observing, interviewing, and documenting. As well as research subjects consisting of PAI teachers, school principals, Muslim students, and Christian students. This research was conducted directly at SMPN 13 Kupang City. From the results of the research carried out, it can be concluded that the task of a teacher is not just teaching but also the teacher can provide examples and motivation that is useful for students, besides that a teacher also has an important role in the community and also religious values. We must, but we will protect it so that in the future there will be no more cases regarding religion in Indonesia